Pendidikan Kesehatan Skrining Hipotiroid Kongenital (SHK) bagi Ibu Nifas di RS PKU Muhammadiyah Temanggung - Ucia Rorin; Ilya Wanawati; Ulya Sesa Febriani; Windayanti, Hapsari; Salafas, Eti; Cahyaningrum (UNIVERSITAS NGUDI WALUYO, 2024)
Congenital hypothyroidism is a deficiency of thyroid hormones in the womb. The incidence of hypothyroidism worldwide is close to 1:3,000. The prevalence in East Asia currently varies from 1:1,000 to 1:6,467, so when viewed from the population, the number of babies with congenital hypothyroidism born each year is close to 40,000. The incidence of congenital hypothyroidism in Indonesia with a birth rate of around 5 million per year, is estimated at 1,765 to 3,200 babies with congenital hypothyroidism and 966 to 3,200 babies with transient congenital hypothyroidism due to iodine deficiency, born every year. Based on interviews conducted with postpartum mothers in the Shofa 1 Room at PKU Muhammadiyah Temangung Hospital, it was found that most postpartum mothers did not know about Congenital Hypoteroid Screening (SHK). The method of community service carried out is health education on Congenital Hypothyroidism (SHK) Screening with leaflet media and filling out pre and post-test questionnaires for postpartum mothers' knowledge about SHK, conducted from March 7-14, 2024 with a total of 25 respondents in the Shofa 1 Room. From this community service, it was found that most of the postpartum mothers had good knowledge as many as 22 people (95%), postpartum mothers with sufficient knowledge as many as 3 people (5%), and postpartum mothers with less knowledge as many as 0 people (0%). ABSTRAK Hipotiroid kongenital merupakan kekurangan hormon tiroid sejak dalam kandungan. Kejadian hipotiroid di seluruh dunia prevalensinya mendekati 1 : 3.000. Prevalensi di Asia Timur saat ini bervariasi dari 1 : 1.000 sampai 1 : 6.467, sehingga bila dilihat dari jumlah penduduk maka bayi dengan hipotiroid kongenital yang lahir tiap tahun mendekati 40.000. Angka kejadian hipotiroid kongenital di Indonesia dengan angka kelahiran sekitar 5 juta per tahun, diperkirakan sebanyak 1.765 sampai 3.200 bayi dengan hipotiroid kongenital dan 966 sampai 3.200 bayi dengan hipotiroid kongenital transien karena kekurangan iodium, lahir setiap tahunnya. Berdasarkan wawancara yang dilakukan dengan ibu nifas di Ruang Shofa 1 di RS PKU Muhammadiyah Temangung, didapatkan sebagian besar ibu nifas tidak mengetahui tentang Skrining Hipoteroid Kongenital (SHK). Metode pengabdian kepada masyarakat yang dilakukan adalah pendidikan kesehatan Skrining Hipotiroid Kongenital (SHK) dengan media leaflet dan melakukan pengisian kuesioner pre dan post test pengetahuan ibu nifas tentang SHK, dilakukan dari tanggal 7–14 maret 2024 dengan jumlah 25 responden di Ruang Shofa 1. Dari pengabdian masyarakat ini didapatkan sebagian besar ibu nifas memilki pengetahuan yang baik sebanyak 22 orang (95%), ibu nifas dengan pengetahuan yang cukup sebanyak 3 orang (5%) dan ibu nifas dengan pengetahuan kurang sebanyak 0 orang (0%).